A Review of Organic Photovoltaic Energy Source and Its Technological Designs - Egidius Rutatizibwa Rwenyagila (International Journal of Photoenergy)
This study reviews and describes some of the existing research and mechanisms of operation of organic photovoltaic (OPV) cells. Introduced first are problems that exist with traditional fossil fuels that result in most of the world energy challenges such as environmental pollution. This is followed by the description of baseline organic solar cell (OSC) structures and materials. Then, some of the existing modelling approaches that have implemented either a one- or a two-dimensional drift-diffusion model to examine OSC structures are reviewed, and their reproducibility is examined. Both experimental and modelling approaches reviewed are particularly important for more and better designed research to probe practical procedural problems associated with OSCs that hinder the commercialization of OPV technology.